International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
The seventh volume of the proceedings of the International Conference on Transportation and Development 2022, held in Seattle, Washington, May 31–June 3, 2022. This collection contains 21 peer-reviewed papers on various transportation modes. Topics include: high-speed rail; multimodal regional systems; bus transit; electric aircraft; and airport planning.